Method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping forming
By preparing samples, cleaning and using a mixture of fluoroboric acid aqueous solution and oxalic acid dihydrate, surface cracks were displayed, and combined with scanning electron microscope observation and measurement of crack spacing, the problem that traditional detection methods are difficult to clearly display surface cracks after hot stamping of aluminum silicon plating is solved, achieving efficient and accurate detection results.
Patent Information
- Application Number
- CN202510260505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional testing methods are difficult to clearly display the tiny cracks on the surface of the aluminum-silicon plating after hot stamping, especially on molded parts of complex shapes, which can easily lead to the peeling or cracking of the plating layer, which cannot accurately reflect the cracking of the plating layer after molding.
Sample preparation, cleaning, and using a mixture of fluoroboric acid aqueous solution and oxalic acid dihydrate as an erosive agent to display surface cracks, and combined with scanning electron microscopy to observe and measure the crack spacing.
It can clearly display the cracks on the surface of the plating after hot stamping of aluminum silicon plating, accurately measure the crack spacing, and has the characteristics of low detection costs, fast, simple and accurate, ensuring that the product quality and performance meet the standards.
Smart Images

Figure CN119880979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating analysis and detection, and in particular to a method for displaying and observing surface cracks of an aluminum silicon coating after hot stamping. Background Art
[0002] In the manufacturing industries such as automobiles and home appliances, aluminum-silicon plates are widely used in hot forming processes because of their good heat resistance, corrosion resistance and aesthetics. However, the high temperature, high pressure and complex stress changes in the hot forming process can easily cause cracks in the coating of aluminum-silicon plates. Surface cracks in the coating will affect many aspects such as product quality, corrosion resistance, and subsequent processability. In the quality control and product testing process, it is extremely important to be able to effectively display and observe these cracks. Traditional detection methods use cross-sectional metallography and direct observation by scanning electron microscope, which are difficult to clearly display these tiny cracks, especially on the surface of complex-shaped molded parts. Cross-sectional metallography can cause the coating to fall off or crack during the sample preparation process, and cannot correctly reflect the cracking of the coating after molding. With the continuous improvement of product quality requirements in industrial production, more accurate and efficient methods are needed to observe and evaluate these surface cracks in the coating to ensure that product quality and performance meet standards, which is very meaningful. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for displaying and observing surface cracks of an aluminum-silicon coating after hot stamping, including sample preparation, cleaning, using an etchant to display surface cracks and scanning electron microscope observation, and measuring crack spacing. The method can simply and clearly display the crack conditions on the surface of the aluminum-silicon coating after hot stamping, and has the characteristics of low cost, fast, simple and accurate detection.
[0004] To achieve this technical purpose, the present invention adopts the following scheme: A method for displaying and observing surface cracks of an aluminum-silicon coating after hot stamping, comprising the following steps: S1. Sample preparation: Use wire cutting machine to cut the sample to be tested; S2. Cleaning the sample: Place the sample in step S1 in alcohol and perform ultrasonic cleaning for 3 to 5 minutes; S3, showing cracks on the surface of the coating after hot stamping: putting the cleaned sample in step S2 into an etchant, corroding for 20 to 120 minutes, taking out the corroded sample, rinsing it with alcohol, and drying it, the etchant is a mixture of a fluoroboric acid aqueous solution and dihydrated oxalic acid; S4. Scanning electron microscope observation and measurement of crack spacing: Place the sample under a scanning electron microscope to scan and observe and measure the crack spacing.
[0005] The preferred embodiment of the present invention is: A method for displaying and observing surface cracks of an aluminum-silicon coating after hot stamping, comprising the following steps: S1. Sample preparation: Use wire cutting machine to cut the sample to be tested. The sample size is 10×10mm~15×15mm; S2. Cleaning the sample: put the sample cut in step S1 into a beaker, add 30 ml of alcohol, drop 2-3 drops of detergent, put the beaker into an ultrasonic cleaner, set the output power of the ultrasonic cleaner to 60-80%, set the temperature to 30-40°C, clean for 3-5 minutes, take out, and rinse the sample with alcohol; S3, showing cracks on the surface of the coating after hot stamping: the cleaned sample in step S2 is placed in an etchant, which is a mixture of 30 ml of a 1%-5% fluoroboric acid aqueous solution and 0.01-0.03 g of oxalic acid dihydrate, and the etchant is corroded for 20-120 minutes; Take out the corroded sample, rinse it with alcohol for 3-5 seconds, and blow dry it with a hair dryer; S4. Scanning electron microscope observation and measurement of crack spacing: Place the sample in step S4 under a scanning electron microscope for observation. Select 15-20KV for high voltage and secondary electron mode for mode. Observe the displayed coarse cracks and the micro cracks between them, and accurately measure the crack spacing.
[0006] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for displaying and observing surface cracks of aluminum silicon coating after hot stamping, including sample preparation, cleaning, displaying surface cracks, scanning electron microscope observation, and measuring crack spacing. A mixture of fluoroboric acid aqueous solution and dihydrated oxalic acid is used as an etchant to display surface cracks, and combined with scanning electron microscope observation, the crack situation of the coating surface after hot stamping of aluminum silicon coating can be clearly displayed, and the crack spacing can be accurately measured. The method has the characteristics of low detection cost, rapidity, simplicity and accuracy. It is of great significance to ensure that product quality and performance meet standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 This is a scanning electron microscope image of the surface cracks shown in Example 1; Figure 2 This is a picture of the crack spacing accurately measured in Example 1; Figure 3 This is a picture of Comparative Example 1 observed using a direct scanning electron microscope; Figure 4 This is a scanning electron microscope image of the surface cracks shown in Example 2; Figure 5 This is a picture of the crack spacing accurately measured in Example 2; Figure 6 A photograph showing cracks using cross-sectional metallographic images for comparative example 2; Figure 7 This is a scanning electron microscope image of the surface cracks shown in Example 3; Figure 8 This is a picture of the crack spacing accurately measured in Example 3; Fig. 9 This is a photo of Comparative Example 3 after HF etching (surface powderization); Fig.10 This is a photo of comparative example 3 after HF etching (falling off at the crack). DETAILED DESCRIPTION
[0008] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific implementation methods, but the present invention is not limited thereto. Example 1
[0009] Take a 1.2mm aluminum-silicon plate for hot stamping, grade 22MnB5, and hot stamping the sample at 930℃ for 3 minutes. The display and observation method of surface cracks after hot stamping includes wire cutting to cut the sample, cleaning the sample surface, displaying the cracks on the coating surface after hot stamping, observing under a scanning electron microscope, and measuring the crack spacing. Specifically: S1. Sample preparation: Take the sample after hot stamping and cut it with a wire cutting machine. The sample size is 10×10mm; S2. Cleaning the sample: put the sample cut in step S1 into a beaker, add 30 ml of alcohol, drop 2 drops of detergent, set the output power of the ultrasonic cleaner to 60%, clean for 5 minutes, take it out, and rinse it with alcohol; The ultrasonic cleaner can be any of the existing equipment. In this application, a KQ-100DE CNC ultrasonic cleaner is used. The output power of the ultrasonic cleaner is set to 60-80%, and its use range is 0-100%. The output power cannot be too high, which will damage the sample surface, and too low will not clean thoroughly. S3, showing cracks on the surface of the coating after hot stamping: The specific operation is to put the sample of step S2 into the following etchant: 30 ml of 1% fluoroboric acid aqueous solution, 0.03 g of oxalic acid dihydrate, corrode for 120 minutes, take out and rinse with alcohol for 5 seconds, and blow dry with a hair dryer; S4. Observe and measure the crack spacing under a scanning electron microscope: The scanning electron microscope can be any of the existing equipment. The ZEISS (SIGMA-HD model) scanning electron microscope is used in this application. The specific operation is to place the sample in step S3 under a ZEISS scanning electron microscope for observation. The high voltage is selected as 15KV, the mode is selected as SE2 mode (secondary electron mode), and the coarse cracks and the micro cracks between them can be clearly displayed by magnifying 72 times. The results are shown in FIG. Figure 1 , the crack spacing can be accurately measured, 246.3 microns, the results are shown in Figure 2 .
[0010] Comparative Example 1: Direct SEM Observation
[0011] Take a 1.2mm aluminum-coated silicon plate for hot stamping, grade 22MnB5, and hot stamping the sample at 930℃ for 3 minutes. Observe the surface cracks directly after hot stamping. Cut a 10×10mm sample with a shearing machine, rinse it with alcohol for 5 seconds, blow dry it with a hair dryer, and observe it under a scanning electron microscope. Even if the magnification is as high as 500 times, only local coarse cracks can be seen, and micro cracks cannot be displayed. The results are shown in Figure 3 . Example 2
[0012] Take a 1.0mm aluminum-silicon plate for hot stamping, grade 22MnB5, and hot stamping the sample at 930℃ for 3 minutes. The display and observation method of surface cracks after hot stamping includes wire cutting to cut the sample, cleaning the sample surface, displaying the cracks on the coating surface after hot stamping, observing under a scanning electron microscope, and measuring the crack spacing. Specifically: S1. Sample preparation: Take the hot stamping sample and cut it with a wire cutting machine. The sample size is 12×15mm; S2. Cleaning the sample: put the sample cut in step S1 into a beaker, add 30 ml of alcohol, drop 3 drops of detergent, set the output power of the ultrasonic cleaner to 70%, clean for 3 minutes, take it out, and rinse it with alcohol; S3, showing cracks on the surface of the coating after hot stamping: The specific operation is to put the sample of step S2 into the following etchant: 30 ml of 3% fluoroboric acid aqueous solution, 0.02 g of oxalic acid dihydrate, corrode for 80 minutes, take it out and rinse it with alcohol for 3 seconds, and blow it dry with a hair dryer; S4. Observe and measure crack spacing under scanning electron microscope: The specific operation is to put the sample in step S3 into ZEISS scanning electron microscope for observation. The high voltage is selected as 20KV and the mode is selected as SE2 mode. The coarse cracks and the micro cracks between them can be clearly displayed. The results are shown in Figure 4 , the crack spacing can be accurately measured, 514.5 microns, the results are shown in Figure 5 .
[0013] Comparative Example 2: Observation of cracks using cross-section metallographic method
[0014] (1) Sample preparation: Take a 1.0 mm hot stamped aluminum-coated silicon plate (grade 22MnB5), cut the full thickness specimen by wire cutting, the specimen size is 15 mm × 15 mm, put the specimen vertically into the hot mounting machine for mounting, the mounted specimen is rough-grinded and fine-grinded with sandpaper, and then polished. Specifically, water and 2.5 μm high-efficiency metallographic polishing agent are evenly sprayed on a 250 mm pressure-sensitive rubber wool polishing cloth, and then polished for 2 minutes at a polishing machine speed of 900 rpm; (2) Cleaning: Rinse with alcohol for 3 seconds and blow dry; (3) Observation under a metallographic microscope: The sample cleaned in step (2) is placed under a ZEISS metallographic microscope for observation. No surface cracks can be observed, only the detached coating and individual cracks can be observed. The result is directly related to the quality of the sample preparation. For details, see Figure 6 . Example 3
[0015] The method for displaying and observing the surface cracks of the aluminum silicon coating after hot stamping includes cutting samples by wire cutting, cleaning the sample surface, displaying the cracks on the coating surface after hot stamping, observing under a scanning electron microscope, and measuring the crack spacing. Specifically: S1. Sample preparation: Take a 1.5mm hot stamped aluminum-silicon plate (grade 22MnB5), cut the sample with a wire cutting machine, the sample size is 10×10mm; S2. Cleaning the sample: put the sample cut in step S1 into a beaker, add 30 ml of alcohol, drop 2 drops of detergent, set the output power of the ultrasonic cleaner to 60%, clean for 4 minutes, take it out, and rinse it with alcohol; S3, showing cracks on the surface of the coating after hot stamping: The specific operation is to put the sample of step S2 into the following etchant: 30 ml of 5% fluoroboric acid aqueous solution, 0.01 g of oxalic acid dihydrate, corrode for 20 minutes, take it out and rinse it with alcohol for 5 seconds, and blow it dry with a hair dryer; S4. Observe and measure crack spacing under scanning electron microscope: The specific operation is to put the sample in step S3 into ZEISS scanning electron microscope for observation. The high voltage is 15KV and the mode is SE2. Even with a very small magnification (78 times), the coarse cracks and the micro cracks between them can be clearly displayed. The results are shown in Figure 7 , the spacing of micro cracks can be accurately measured, which is 171.8 microns. Figure 8 .
[0016] Comparative Example 3: Observation of cracks using HF etching agent
[0017] The display and observation method of surface cracks of aluminum silicon coating after hot stamping includes wire cutting to cut samples, cleaning sample surface, corroding the surface with HF, and observing under scanning electron microscope. Since HF has a rapid and strong corrosive effect on silicon-rich phase, after the aluminum silicon coating is formed by high-temperature hot stamping, HF has a strong corrosive effect on the silicon-containing oxide on the surface, making the cracks wider, and at the same time, the surface is corroded and powdered, and even the coating falls off at the cracks. The details are as follows: S1. Sample preparation: Take a 1.5mm hot stamped aluminum-silicon plate (grade 22MnB5), cut the sample with a wire cutting machine, the sample size is 10×10mm; S2. Cleaning the sample: put the sample cut in step S1 into a beaker, add 30 ml of alcohol, drop 2 drops of detergent, set the output power of the ultrasonic cleaner to 60%, clean for 4 minutes, take it out, and rinse it with alcohol; S3, showing cracks on the surface of the coating after hot stamping: The specific operation is to put the sample of step S2 into the following etchant: 30 ml of 5% HF aqueous solution, corrode for 20 minutes, take it out and rinse it with alcohol for 5 seconds, and blow it dry with a hair dryer; S4. Observe and measure the crack spacing under a scanning electron microscope: The specific operation is to place the sample in step S3 under a ZEISS scanning electron microscope for observation. The high voltage is 15KV and the mode is SE2. It can be seen that the dense coating is partially powdered and the cracks are partially detached. Fig. 9 , Fig.10 .
[0018] Compared with the prior art, the present invention can clearly display the coarse cracks and micro cracks on the surface of the aluminum silicon coating after hot stamping, and can accurately measure the crack spacing. The present invention uses a mixed solution of fluoroboric acid aqueous solution and dihydrated oxalic acid as a corrosive solution, which can not only clearly display the surface crack situation, but also does not destroy the crack structure. It has the characteristics of low detection cost, fast, simple, accurate and safe, and can accurately reflect the crack situation after hot stamping, which is of great significance for later processing.
[0019] Finally, it should be noted that the above are only preferred embodiments of the present invention. Of course, those skilled in the art can make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and their equivalent technologies, they should be considered to be within the scope of protection of the present invention.
Claims
1. A method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping, characterized in that: The following steps are involved: S1. Sample preparation: Use wire cutting machine to cut the sample to be tested; S2. Cleaning the sample: Place the sample in step S1 in alcohol and perform ultrasonic cleaning for 3 to 5 minutes; S3, showing cracks on the surface of the coating after hot stamping: putting the sample cleaned in step S2 into an etchant, corroding for 20 to 120 minutes, taking out the corroded sample, rinsing it with alcohol, and drying it, wherein the etchant is a mixture of a fluoroboric acid aqueous solution and dihydrated oxalic acid; S4. Scanning electron microscope observation and measurement of crack spacing: Place the sample under a scanning electron microscope to scan and observe and measure the crack spacing.
2. The method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping according to claim 1 is characterized in that: The sample size in step S1 is 10×10 mm to 15×15 mm.
3. The method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping according to claim 1, characterized in that: The specific operation of cleaning the sample in step S2 is: put the sample cut in step S1 into a beaker, add 30 ml of alcohol, drip 2 to 3 drops of detergent, put the beaker into an ultrasonic cleaner, set the output power of the ultrasonic cleaner to 60 to 80%, set the temperature to 30-40°C, clean for 3 to 5 minutes, take out, and rinse the sample with alcohol.
4. The method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping according to claim 1, characterized in that: In step S3, the etching agent is a mixture of 30 ml of a 1% to 5% mass concentration fluoroboric acid aqueous solution and 0.01 to 0.03 g of oxalic acid dihydrate.
5. The method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping according to claim 1, characterized in that: In step S3, the alcohol is rinsed for 3 to 5 seconds and then dried with a hair dryer.
6. The method for displaying and observing surface cracks of aluminum-silicon coating after hot stamping according to claim 1, characterized in that: The specific operation of step S4 is: put the sample of step S4 into a scanning electron microscope for observation, select 15-20KV for high voltage, select secondary electron mode for mode, observe the displayed coarse cracks and the micro cracks between them, and accurately measure the spacing between the cracks.
Citation Information
Patent Citations
Method for etching surface crack defect of sample
CN106018046A
Cleaning method for removing oxide layer on surface of silicon material
CN114653667A
Metallographic corrosion liquid and metallographic corrosion method for 5049 aluminum alloy
CN114964985A
Sample preparation method for metallographic structure of rolled product and corrosive agent
CN118329554A